The Influence of Monetary Policy Instruments on Economic Growth in Indonesia: Comparison between Islamic and Conventional Monetary Instruments - Ririn Riani; Imron HR (Ekonomi Islam Indonesia, 2022)
Monetary policy has an important role in a country's economy. The central bank plays a role in carrying out monetary policy for price stability through various mechanisms. This study aims to determine the contribution of conventional and Islamic monetary instruments to economic growth in Indonesia. This study uses time series data from January 2013 to December 2020 and is analyzed using the Vector Error Correction Model (VECM) method. From the results of the analysis that has been carried out, it can be seen that in the long run, interest rates, exchange rates, the Islamic Interbank Money Market (PUAS), and Bank Indonesia Sharia Certificates (SBIS) have a significant effect on economic growth. IRF results show that exchange rates react negatively to shocks from GDP over 48 periods. The FEVD results show that the interbank money market (PUAB) has the most significant contribution after GDP in explaining the 10 percent variability of economic growth.